Laws And Regulatory Framework On Internet Banking - Malaysian Perspective. - Hong, Yeoh Suan (2003)
This paper will try to explore the current status of Internet banking in malaysia and its regulatory framework together with the security and privacy issues of Internet Banking in the light of the Banking and Financial Institutions ACt(BAFIA) 1989, the central Bank's Minimum Guideline on the Provisions of Internet Banking Services by Licensed Institutions 2000, Computer Crimes Act 1997, and the Personal Data protection Bill 1998. This paper will make some comparison between the Malaysian Internet Banking laws and internet banking laws in United Kingdom and United States.